Parental leave in European companies establishment survey on working time 2004-2005 - Anxo, Dominique. (Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2006)
Parental leave - as well as other forms of extended leave, such as leave to care for sick children or other adult family members - constitutes a major policy component for promoting work-life balance for employees with caring responsibilities. Although the right to parental leave has been established in all European Union Member States, endorsed by the EU directive on parental leave, large differences continue to exist between countries with regard to policy detail and patterns of take-up of such leave by parents. Research on parental leave is still limited in many countries, and where it does exist it tends to focus on analysing patterns of take-up among employees and the impact of leave on employment patterns, and the division of care responsibilities between mothers and fathers. Information about company practices and attitudes towards parental leave remains relatively limited; and for some countries, it is virtually non-existent (Plantenga and Remery, 2005).vernment about the direction of public policies, as well as interpreting these policies for their members. Thus, they have an important role to play in European society.